THE EFFECT OF USING SIX THINKING-HATS-STRATEGY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMP TELKOM PEKANBARU IN COMPREHENDING RECOUNT TEXTS - Maqfira, Arinda Arum; Supriusman, Supriusman; Syarfi, M. (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This pre-experimental study was conducted by using One-Group Pretest-Posttest design to find out whether or not there is a significant effect of using ‘Six Thinking Hats Strategy’ on the ability of the second year students of SMP Telkom Pekanbaru in comprehending recount text. The sample of the research was 31 students of class VIII.b and obtained by using simple random sampling technique. 25 multiple choices of recount text was the instrument of the test. The students’ scores were analyzed by using Microsoft Excel 2010 and Statistical Product and Service Solution (SPSS) 23.0 for windows. The collected data were analyzed by using t-test formula. The results showed that the mean score of post-test was higher than pre-test (64.64>52.25). Then, it also showed that t-test was higher than t-table (10.51>2.04) at significance level of 5%. Therefore, Alternative Hypothesis (Ha) is accepted and Null hypothesis (Ho) is rejected. It can be concluded that there is a significant effect of using‘Six Thinking Hats Strategy’ on the ability of the second year students of SMP Telkom Pekanbaru in comprehending recount text.Key Words: Effect, Six Thinking Hats, Recount Text